Multiobjective adaptive current search for engineering design optimization - Suwannarongsri, Supaporn; Puangdownreong, Deacha (Engineering and Applied Science Research, 2017)
This article proposes a multiobjective adaptive current search (MoACS) as a powerful metaheuristic optimization technique for solving multiobjective optimization problems. MoACS is a newly modified version of the current search (CS) developed from the behavior of current in an electrical network. In this study, the MoACS is developed and validated against three standard multiobjective test functions. Results obtained from the MoACS are compared with those obtained by five well-known algorithms from the literature. Then, the MoACS is applied to the design of two real-world multiobjective engineering optimization problems, i.e., welded beam design and disc brake design. It was found that MoACS provided very satisfactory solutions and had quite smooth Pareto fronts for all of the problems.